A diastereoselective synthesis of functionalized bis-spirorhodanine-linked cyclopentanes via C(sp3)–H activation. Issue 30 (26th July 2018) - Yavari, Issa; Naeimabadi, Maryam; Halvagar, Mohammad R.
Abstract: A diastereoselective synthesis of bis-spirorhodanine-linked cyclopentane derivatives via the [2 + 2+1] cycloaddition reaction between alkyl ( Z )-2-(3-alkyl-4-oxo-2-thioxothiazolidin-5-ylidene)acetates (alkylidenerhodanines) and azomethine ylides, prepared in situ from iodine mediated reaction of 2-methylquinoline and pyridine in the presence of base, has been developed. The structure of a typical product was confirmed by X-ray crystallography. Graphical abstract: